Memoranda during the war eaudiobook from specimen days. - Whitman, Walt (Recorded Books Inc., 1988)
"The real war will never get in the books," Walt Whitman wrote in this diary he kept during the Civil War. Whitman chronicled his visits to Washington, D.C. hospitals where he comforted wounded men and assisted nurses and doctors. This journal, written by one of America's greatest poets and writers, captures the details and ironies of war.